NASIONALISME & GENDER DALAM PENERJEMAHAN: IDEOLOGI DALAM PENERJEMAHAN - Ardi, Havid (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2009)
The ideology in the translation subject differs from the ideology in social subject. The process of translating is influenced by the ideology of the translator. There are two ideologies in the translation practice, they are: foreignization and domestication. In fact, there is no a pure foreignization or domestication translation. There is only a tendency to use a foreignization or domestication ideology in translation. Instead of that, the societyâ€™s vision also determines what the translation should be.Â Keywords/ phrases: translation ideology, foreignization, domestication